Exploring STEM Education for Real-World Climate Change Concerns to Empower Students as Change Agents - Maspul, Kurniawan Arif (Indonesian Journal Publisher, 2024)
This article explores the application of STEM (Science, Technology, Engineering, and Mathematics) curriculum to real-world problems, with a focus on increasing the relevance and community involvement in climate change projects. Students are empowered to actively contribute to the resolution of problems in their communities when they are involved in community-based activities. This method encourages student involvement, critical thinking, and a sense of social responsibility. STEM projects must be aligned with suitable grade levels and selected major real-world problems to be successful and appropriate. Climate change was chosen as a real-world topic because of its urgency and far-reaching repercussions, which necessitate multidisciplinary approaches and innovative solutions. Students gain critical thinking skills, problem-solving ability, and a sense of environmental stewardship by immersing them in the subject of climate change. The article outlines a qualitative approach that involves literature review, group discussions, and educator observations to lay a solid theoretical foundation and ensure the strategy's success. The debate focuses on the significance of meaningful educational experiences, ways for preparing educators for community involvement, and the need to recognize and celebrate accomplishments. Students get a deeper knowledge of scientific principles while developing the skills and mindset to address global concerns as responsible global citizens by integrating STEM education, community involvement, and climate change.